Chemical and Physical Properties of Selected Biochar Types and a Few Application Methods in Agriculture - Evan Bassam Dayoub; Zoltán Tóth; Gábor Soós; Angéla Anda (Agronomy)
Biochar, a carbon-rich by-product of organic matter pyrolysis, has a variety of physiochemical properties beside a variety of applications. This review highlights some physical and chemical characteristics of herbaceous, woody, and sewage waste biochar under different pyrolysis conditions, as well as soil and foliar applications of biochar. The controlling role of pyrolysis temperature was the reason for selecting the discussed biochar types in the study. This review concludes that increasing pyrolysis temperature mainly raised the values of some chemical properties of the biochar, such as pH, electrical conductivity (EC), ash content, total phosphorus (TP), and a few values of physical properties like porosity and specific surface area (SSA). On the other hand, yield and total nitrogen (TN) decreased with rising pyrolysis temperature. Among biochar application methods to soil, mixing biochar with soil before planting is one of the best methods of application, and in most cases, biochar reapplication improved soil properties, while foliar application of biochar has positive effects on plant growth and yield parameters, ranging from low rates to the highest ones.